The shape of the river : long-term consequences of considering race in college and university admissions - Bowen, William G.; Bok, Derek Curtis (William G. Bowen Ser., 2019)
First published in 1998, William Bowen and Derek Bok's The Shape of the River became an immediate landmark in the debate over affirmative action in America. It grounded a contentious subject in concrete data at a time when arguments surrounding it were characterized more by emotion than evidence--and it made a forceful case that race-conscious admissions were successfully helping to promote equal opportunity. Today, the issue of affirmative action remains unsettled. Much has changed, but The Shape of the River continues to present the most compelling data available about the effects of affirmative action. Now with a new foreword by Nicholas Lemann and an afterword by Derek Bok, The Shape of the River is an essential text for anyone seeking to understand race-conscious admissions in higher education.